Transient Heat Transfer Modeling of SERF Co-Magnetometer Atomic Ensemble Based on the Thermoelectric Analogy Method - Jiaqi Wu; Feng Liu; Lihong Duan; Shaowei Lv; Xihui Dou; Wei Quan (Photonics)
Bias instability is one of the most critical factors in the performance of spin-exchange relaxation-free (SERF) co-magnetometers. Previous studies on SERF co-magnetometers have shown that changes in the atomic ensemble temperature can lead to variations in the alkali metal atom density, which in turn affect the optical rotation angle and light shift, ultimately influencing the system’s stability. Building on this understanding, this paper introduces the thermoelectric analogy method for the first time in the transient heat transfer analysis of SERF co-magnetometer atomic ensembles. Using this method, the primary factors affecting the atomic ensemble temperature in a SERF co-magnetometer were analyzed, and transient heat transfer models were established for the following processes: the interaction between the non-magnetic electric heating system and the atomic ensemble temperature, laser heating of the atomic ensemble by the optical system, and the effect of environmental temperature changes on the non-magnetic electric heating system. These models were experimentally validated through active temperature variation experiments. The experimental results show that the proposed transient heat transfer models accurately describe the related heat transfer processes of the atomic ensemble, with model fitting accuracy exceeding 98%. This lays a solid foundation for the high-precision closed-loop control of the atomic ensemble temperature in SERF co-magnetometers and provides valuable insights for the structural design and engineering applications of SERF co-magnetometers.